From Normative to Empathetic Evaluation: Reconfiguring Appraisal in Indonesian Advertising Discourse - Robith Khoiril Umam; Djatmika Djatmika; Sumarlam Sumarlam; Ristiya Krisnawati (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
Public advertisements are often not just highlighting the benefits or advantages of a product or service. They also serve as a source for sharing values, ideologies and hierarchical relationship patterns between producers and users. This study aims to examine evaluative language in Indonesian advertisements across decades using appraisal theory. The focus of the study is on comparing advertisements from the 1990s and contemporary digital advertisements, using data drawn from printed advertisements from the 1990s and recent digital advertisements representing Indonesian child-nutrition and food advertising discourse. Data were collected from printed advertising materials, YouTube, and Instagram captions that were transcribed validly, then analysed qualitatively by using appraisal theory. The results of the analysis show a significant shift in appraisal patterns. Advertisements in the 1990s were dominated by normative and collective affect, hierarchical judgement of the role of mothers, and symbolic appreciation that emphasised achievement and obedience as indicators of a child's success. In contrast, current digital advertisements employ reflective psychological affect, more empathetic and implicit judgements, and evidential appreciation supported by nutritional data and emotional metaphors. The use of graduation is also increasingly intensive to emphasise the progress and long-term impact of the product. These findings suggest that changes in advertising language not only reflect shifts in marketing strategies but also indicate changing ways in which parenting and child development are discursively framed in Indonesian advertising. The study provides an empirical mapping of diachronic shifts in evaluative language in Indonesian advertising context, from a normative and collective pattern toward a more reflective and empathetic evaluative orientation within the appraisal framework.